Long‐Term Follow‐Up of Idiopathic Ventricular Fibrillation in a Pediatric Population: Clinical Characteristics, Management, and Complications. Issue 9 (7th May 2019) - Frontera, Antonio; Vlachos, Konstantinos; Kitamura, Takeshi; Mahida, Saagar; Pillois, Xavier; Fahy, Gerard; Marquie, Christelle; Cappato, Riccardo; Stuart, Graham; Defaye, Pascal; Kaski, Juan Pablo; Ector, Joris; et al.
Abstract : Background: The natural history and long‐term outcome in pediatric patients with idiopathic ventricular fibrillation (IVF) are poorly characterized. We sought to define the clinical characteristics and long‐term outcomes of a pediatric cohort with an initial diagnosis of IVF. Methods and Results: Patients were included from an International Registry of IVF (consisting of 496 patients). Inclusion criteria were: (1) VF with no identifiable cause following comprehensive analysis for ischemic, electrical or structural heart disease and (2) age ≤16 years. These included 54 pediatric IVF cases (age 12.7±3.7 years, 59% male) among whom 28 (52%) had a previous history of syncope (median 2 syncopal episodes [interquartile range 1]). Thirty‐six (67%) had VF in situations associated with high adrenergic tone. During a median 109±12 months of follow‐up, 31 patients (57%) had recurrence of ventricular arrhythmias, mainly VF. Two patients developed phenotypic expression of an inherited arrhythmia syndrome during follow‐up (hypertrophic cardiomyopathy and long QT syndrome, respectively). A total of 15 patients had positive genetic testing for inherited arrhythmia syndromes. Ten patients (18%) experienced device‐related complications. Three patients (6%) died, 2 due to VF storm. Conclusions: In pediatric patients with IVF, a minority develop a definite clinical phenotype during long‐term follow‐up. Recurrent VF is common in this patient group.